Entre a solidariedade e o risco: sindicatos e fundos de pensão em tempos de governo Lula - Jardim, Maria Aparecida Chaves (Universidade Federal de São Carlos, 2007)
The social inclusion projects of President Lula s first term accordingly proceeded through the market, as for instance: the Microcredit project, Banco Popular do Brasil (Brazil s Popular Bank) and especially the pension funds. Social inclusion by way of market is part of PT s political policies, which surveys have provisionally considered as moralization and/or domestication of capitalism, seeing that it strives to apply the money from speculation into productive activities that are capable of generating employment and income for workers. The moralization and/or domestication of capitalism is perceptible in the creation and management guidelines of the pension funds, which became consolidated as a great concern in the Federal Government s program, the three central unions of the country (especially CUT) and the labor unions, especially in the banking and electricity federations. The interaction among the syndicalists and former syndicalists in the Lula Government, businessmen from the pension funds sector and the Federal Government, bespeaks the complicity of interests and the convergence of the elite around the precise configuration of the pension funds. Thus, supported by the discourse of social responsibility, ethical investment, democratic management of the funds, protection of workers savings and the fight against capitalism, by means of their own instruments (domestication of capitalism), the Brazilian syndicalists have expanded accumulated legitimacy to the financial area in the workers scope. Therefore, their argument on management/protection of workers savings is justified as morally legitimate. Taking into account the aforementioned context, the present doctorate thesis set out to understand the social convention changes that the Brazilian syndicalism undergoes, the ambiguities and contradictions of such syndicate actions and the factual role and power our syndicates command. By the same token, it sought to comprehend the social inclusion policies by means of the market of the Lula Government. Lastly, it placed emphasis on the international ideas regarding the pension funds project, as well as the new institutionalizations created by the market s consolidation of pension funds in Brazil. The present work was theoretically influenced by Bourdieu, Mary Douglas, Marcel Mauss, Robert Castel, among renowned professionals of the Brazilian and international Social Sciences. Empirically, interviews were conducted with syndicalists, members of the Lula Government and those who oppose the pension funds project, in addition to observation participation in the events of this sector. Moreover, field work was carried out in central unions in France
Keywords: Sindicalismo; Sociologia do trabalho; Sociologia econômica; Silva, Luiz Inácio da, 1945; Mercado financeiro; Pension funds; syndicates/labor unions; Moralization - domestication of capitalism; Lula Government; New syndicate strategies; CIENCIAS HUMANAS